2020
DOI: 10.21203/rs.3.rs-78728/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cerebrospinal Fluid Biomarkers of Neuroinflammation in Children with Hydrocephalus and Shunt Malfunction

Abstract: Background: Cerebrospinal fluid (CSF) shunt systems fail approximately 30% of the time within the first year of shunt implantation, while 98% of all patients with hydrocephalus (HCP) will suffer shunt failure in their lifetime. Perhaps due to the heterogeneity in etiology or the unique environment housing CSF shunt systems, the underlying reasons for shunt failure continue to elude researchers and clinicians. Still, obstruction remains the most common reason for shunt failure and it is vital to understand what… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…Proteomic analysis of CSF showed that the expression levels brinogen, carbonic anhydrase -I (CA-I), peroxidase − 2(Prx-2), hemoglobin α and β chains, transferrin (TF), and N-terminal haptoglobin (HP) were signi cantly different from those of the control group [29]. In addition, interleukin (IL)-10, IL-6, IL-8, matrix metalloproteinase (MMP)-7, and MMP-9 levels were signi cantly elevated in the CSF protein analysis of PHH [30,31]. A new hypothesis on the cause of hydrocephalus suggests that part of the absorption and secretion of CSF occurs on the intraventricular membrane, and in some events, hydrocephalus is caused by changes in the osmotic pressure of the CSF [32][33][34].…”
Section: Pathogenesis Of Phhmentioning
confidence: 98%
“…Proteomic analysis of CSF showed that the expression levels brinogen, carbonic anhydrase -I (CA-I), peroxidase − 2(Prx-2), hemoglobin α and β chains, transferrin (TF), and N-terminal haptoglobin (HP) were signi cantly different from those of the control group [29]. In addition, interleukin (IL)-10, IL-6, IL-8, matrix metalloproteinase (MMP)-7, and MMP-9 levels were signi cantly elevated in the CSF protein analysis of PHH [30,31]. A new hypothesis on the cause of hydrocephalus suggests that part of the absorption and secretion of CSF occurs on the intraventricular membrane, and in some events, hydrocephalus is caused by changes in the osmotic pressure of the CSF [32][33][34].…”
Section: Pathogenesis Of Phhmentioning
confidence: 98%